Iowa Birdline update, May 28, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for May 28, 1990. Highlights of the update include sightings of a nesting Cooper's Hawk, an immature Broad-winged Hawk, a Eurasian Tree Sparrow, and a Common Loon. Also of note was the near completion of passerine migration, with the exceptions of a few late Warblers and Flycatchers. Epson - sheet feed/flatbed